SOCIAL ATTITUDES AND BEHAVIOUR OF DOG OWNERS TO NEUTERING IN SELECTED CLINICS FROM GWAGWALADA AND ABUJA MUNICIPAL AREA COUNCILS, FCT, NIGERIA - Umeakuana, Paschal U.; Ajogi, Donken I.; Egwu, Grace E.; Godwin, Enid; Ajayi, Christiana F.; Egwu, Godwin O. (FUDMA Journal of Sciences, 2025)
Neutering is an important aspect of responsible dog ownership, contributing to population control, reduced roaming, and the prevention of behavioural and reproductive disorders. However, acceptance of the procedure varies across communities and is influenced by sociocultural and educational factors. This study assessed the knowledge, attitudes, and neutering practices of dog owners attending six private veterinary clinics in Gwagwalada and Abuja Municipal Area Councils, FCT, Nigeria, between May and November 2024. A structured questionnaire was administered to 150 respondents to obtain information on educational level, purpose of dog ownership, awareness of neutering, and willingness to undertake the procedure. Most respondents had tertiary education (113/150; 75.3%), followed by secondary (32/150; 21.3%) and primary education (5/150; 3.3%). Security was the major reason for dog ownership (86/150; 57.3%), followed by companionship (46/150; 30.7%). Vaccinated dogs accounted for 131/150 (87.3%). Awareness of neutering was reported by 115/150 (76.7%). Among male dogs, 18/82 (22.0%) had been castrated, while only 4/68 (5.9%) females were spayed. Of owners with intact dogs, 29/128 (22.7%) were willing to neuter in the future, whereas 99/128 (77.3%) were unwilling. Educational level was significantly associated with knowledge of neutering (χ² = 20.77, df = 2, p < 0.001), with tertiary-educated owners more aware than others (OR = 5.35; 95% CI: 2.34–12.21). Male dogs were more likely to be castrated than females (OR = 4.50; 95% CI: 1.44–14.04; p = 0.011). Despite high awareness, neutering uptake remains low. Improved public education and veterinary-led advocacy are recommended to enhance acceptance.